Clinicopathological Implications of Proteinuria after Long-Term Isolated Hematuria due to Thin Basement Membrane Nephropathy and Focal Segmental Glomerulosclerosis - Ryo Togashi; Yoshikazu Nemoto; Kaito Waki; Michito Nagura; Shigeyuki Arai; Yoshifuru Tamura; Yasutoshi Oshima; Fukuo Kondo; Ryuji Ohashi; Shunya Uchida; Shigeru Shibata; Yoshihide Fujigaki (Case Reports in Nephrology)
A 45-year-old obese man presented with persistent hematuria for 21 years. At the age of 37, he developed hypertension and proteinuria which later increased up to 1.6 g/g creatinine. Kidney biopsy revealed thin basement membrane nephropathy (TBMN) and focal segmental glomerulosclerosis (FSGS), which explained his urinary abnormalities. Although a subgroup of TBMN can be complicated by FSGS, his FSGS was associated with obesity because of its histological features. Reduction of body weight and increasing a dose of angiotensin-receptor blocker could transiently reduce the amount of proteinuria. Clinicopathological implications of proteinuria after long-term hematuria by TBMN and FSGS were further discussed.